Algorithm for Calcium Deficiency Correction in Young Children with Food Allergy Manifestations - O.V. Kryazhev; L.S. Ovcharenko; A.O. Vertegel; I.V. Samokhin; T.G. Andriyenko; N.V. Zhikhareva (Zaslavsky O.Yu., 2014)
Objective - to develop algorithm for calcium deficiency correction in young children with food allergy (FA) manifestations. Materials and Methods. We have examined 150 children aged 1 to 3 years age with FA and sensitization to cow's milk protein and in two study groups: 1) I group - children with FA manifestations and the laboratory signs of calcium deficiency (n = 56); 2) II group - children with FA manifestations without the laboratory signs of calcium deficiency (n = 94). The level of total calcium, inorganic phosphorus and vitamin 25(OH)D3 in blood serum were investigated. Results. As a result of inspection 150 children with FA, we have found decline of serum calcium concentration in 56 children (37.3 %) (fluctuations of parameters from 2.08 to 2.24 mmol/l). The same situation was marked in relation to the level of serum inorganic phosphorus in children of I group (fluctuations of parameters from 1.42 to 1.54 mmol/l). When analyzing the content of vitamin D3 in blood serum, it was discovered, that in children from the study groups this index was within the limits of age-dependent norm (fluctuations of indexes from 24.21 to 26.81 ng/ml). There has been developed an algorithm of differentiated therapeutic and prophylactic measures, including localization, fixation and elimination of causally significant allergens (hypoallergic diet, sorbents), anti-inflammatory therapy (antihistamines, inhibitor of mast cell degranulation, local therapy), correcting therapy for disorders of osteogenesis processes. After the conducted correction, normalization of indexes of total calcium and inorganic phosphorus was marked in the blood serum of children from I study group has been noted. Conclusion. Developed algorithm for differentiated therapeutic and prophylactic measures enables to reduce of activity of allergic inflammatory process and to normalize indexes, characterizing the processes of osteogenesis in young children with food allergy.